Socrates and Business Ethics. Considerations on the ethical origins of responsibility - Podrez, Ewa (Annales. Etyka w Życiu Gospodarczym, 2019)
The presented work attempts to show a link between business and global responsibility, and the Socratic idea of self-knowledge. Today’s ethics discusses the fundamental issues of man’s place in the world. The human existence is one of the causes of the contemporary crisis. This crisis between man and the world obliges us to raise a radical question of the ethical origins of individual and global responsibility for the quality of life and the future of human generations. This question requires going back to the historical and ethical considerations about the Socratic project of the good life. The starting point for Socratic ethics is an inter-personal and inner-personal dialogue; the subsequent result is man’s practical wisdom of how to build his life with others. Socrates argues that the key issue of responsibility is the awakening of self-awareness and the way to achieve this objective is through dialogue.